ANALISIS KEPUTUSAN NASABAH DALAM MEMILIH JENIS BANK: PENERAPAN MODEL REGRESI LOGISTIK BINER (STUDI KASUS PADA BANK BRI CABANG BALIKPAPAN) - Saiful Ghozi; Ramli Ramli; Asri Setyani (MEDIA STATISTIKA, 2018)
This paper analyze factors that influence customer preference between conventional and sharia bank, and which factor is the most dominant. The study was conducted in Balikpapan city from May 2017 until August 2017. The sample is 25 customers of BRI Sharia and 31 customers of conventional BRI. Statistical analysis model used in this paper is Binary Logistics Regression. There are 8 predictor variables to be analyzed to know their effect to customer decision in choosing bank between sharia bank and conventional bank. The variables are: knowledge of respondents about sharia bank (X1), knowledge of respondents about the difference between conventional and sharia banks (X2), knowledge of respondents about products offered by sharia bank (X3), promotion of sharia bank via printed media (X4), promotion of sharia bank via electronic media (X5), promotion of sharia bank in social activities (X6), the customer's efforts to observe religious orders (X7), and the customer's efforts to avoid the religious prohibitions (X8). The results of individual significance test indicate that knowledge of respondents about sharia bank, and promotion of sharia bank through electronic media has significant effect to the customer’s decision in choosing bank. And the most significant effect is promotion through electronic media (X5). Keywords : binary logistic regression, decision, sharia bank